2013
DOI: 10.4293/108680813x13654754535115
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Laparoscopic Sacrocervicopexy for Apical Support of Pelvic Organ Prolapse

Abstract: Laparoscopic sacrocervicopexy appears to be an effective option for sexually active women with pelvic organ prolapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Several authors stressed the role of an adequate colposuspension or cervical suspension at the time of hysterectomy in patients with POP [7,8,19,20]. Sacrocolpopexy in addition to TLH is associated with an increased risk of mesh exposure at the site of the vaginal cuff (incidence between 0.8% and 9%) [19,20]. Conversely, Rosati et al [19] showed an alternative technique involving LSH and the suspension of the cervical stump to the anterior longitudinal ligament of the sacrum.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Several authors stressed the role of an adequate colposuspension or cervical suspension at the time of hysterectomy in patients with POP [7,8,19,20]. Sacrocolpopexy in addition to TLH is associated with an increased risk of mesh exposure at the site of the vaginal cuff (incidence between 0.8% and 9%) [19,20]. Conversely, Rosati et al [19] showed an alternative technique involving LSH and the suspension of the cervical stump to the anterior longitudinal ligament of the sacrum.…”
Section: Discussionmentioning
confidence: 96%
“…Sacrocolpopexy in addition to TLH is associated with an increased risk of mesh exposure at the site of the vaginal cuff (incidence between 0.8% and 9%) [19,20]. Conversely, Rosati et al [19] showed an alternative technique involving LSH and the suspension of the cervical stump to the anterior longitudinal ligament of the sacrum. This approach showed a low recurrence rate, absence of mesh erosion, and preservation of an adequate length of the vaginal canal.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Three different approaches have been introduced to repair the pelvic floor such as abdominal, vaginal, and laparoscopic techniques. Hysterectomy is still considered to be the standard procedure for correcting uterovaginal prolapse ( 3 ) ; however, in the majority of cases, hysterectomy does not overcome abnormalities associated with weakened pelvic support structures such as uterosacral and cardinal ligaments ( 4 ) . Additionally, due to the belief that the uterus plays a role in sexual satisfaction, an increasing number of women avoid undergoing hysterectomy ( 5 ) .…”
Section: Introductionmentioning
confidence: 99%
“…The incidence is approximately 11.6% when associated with hysterectomy due to prolapse and 1.8% associated with other causes of hysterectomy. The reported prevalence rates ranged from 0.2% to 43%, however, up to 10% are usually considered to be more realistic [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%